Considerações sobre o “eu” na Fenomenologia de Investigações Lógicas - Vieira Curvello, Flávio (Sofia, 2024)
This article examines Husserl’s theses on the "ego" in the first edition of the Logische Untersuchungen. While the concept of a "pure ego" becomes significant in the later transcendental developments of his thought, the origins of phenomenology reveal a clear rejection of such an ego. In a more detailed analysis of the only data that can be phenomenologically recognized as an "ego," Husserl differentiates between the "empirical ego" and the "ego as a phenomenological unity of lived experiences." This paper aims to clarify Husserl’s arguments for rejecting the first concept and elucidating the latter two, as well as exploring their interrelation and hierarchy. In doing so, I seek to enhance our understanding of the theoretical position of the "ego" in the origins of phenomenology and its implications in subsequent phases of the method.